A Review on Fabrication and Application of Tunable Hybrid Micro–Nano Array Surfaces. Issue 6 (22nd January 2023) - Li, Chao; Yang, Junjun; He, Wenjun; Xiong, Mengyuan; Niu, Xinsheng; Li, Xiaoyan; Yu, Deng‐Guang
Abstract: The wettability and adhesion of biological surfaces often depend on their periodically arranged hybrid micro–nano array structures. Various fabrication processes are designed to mimic biomimetic micro–nano array surfaces. This review summarizes the types of micro–nano array structures and analyzes fabrication methods based on top‐down and bottom‐up construction, including templating, etching, self‐assembly, and electrospinning/electrospraying. This review focuses on the shape reconfiguration of surface micro–nano array structures under physical stimuli, as well as the changes in material surface properties during the reconfiguration process. In addition, the applications of biomimetic micro–nano array composite surfaces in the fields of droplet transport, adhesion properties, sensors, and soft robotics are also discussed, and the current challenges and prospects in this field are identified. Abstract : The combination of top‐down and bottom‐up approaches enables the fabrication of surfaces with hybrid micro–nano array structures. The tunable micro–nanostructures of smart surfaces respond to physical stimuli such as mechanical force, temperature, light, electricity, and magnetism, which have broad application prospects in the fields of wettability regulation, droplet transport, sensors, and soft robotics.